(3ef fhGOQ eSGFd GdWH eeG EPG ESJYedgG GdWHjH ZjQ GdeGgQ CfcQgGs
(3ChdgG (B:s
(3GdChdi bGd GdEScfOQGfi Ef GdHdGPQ jhdO GdLPGe hGMJQGb GdOe hGdHQU hdjS jYfi HGdHQU gfG GdHQU GdPjf Schf ef GdHdZ Hd GdPi jchf ef GdeQI GdShOGA , hgh CShO Gddhf s
(3BNQgG (B:s
(3eSCdI PcQ GdQGRi ai cJGH GdMejGJ , Cf Mei ShfhNhT JSei GdeSefI , hbGd Ef HOf UGMHgG jZdX JeJ GdeSGFd s
(3Vef eLehY s
(3GfXQgG eY GdWH GdbTGdi Qbe (B"581"s
(3hgj SJ YTQI eSCdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B250 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs